ANALISIS FASILITAS TERHADAP KINERJA GURU DI SD NEGERI 018 RAMBAH HILIR - Irawan, Weldi (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
ABSTRACTWeldi IRAWAN. 1125020.2015. Analysis Facility Performance of Teacher in Elementary School 018 Rambah Hilir. First Advisor: (Seprini, SE.MM), and Second Advisor (Hamdi Sari Maryoni, SE.M.Ec.Dev.).The objectives of this research were to determine analysis facility performance of teachers in Elementary school 018 Rambah Hilir. This research was conducted in Elementary school 018 Rambah Hilir. The research method is quantitative descriptive, which is a way of analyzing the data available on the object of research and compare with the theory related to the problems. The samples used were 9 people. The technique of collected data through observations, interviews and questionnaires. Coefficient constant and variable coefficients based on simple linear regression test results obtained by the regression equation: Y = 48.567 + 0.592 X1. The results showed that the facility is quite good effect on the performance of teachers in Elementary school 018 Rambah Hilir is 72.5% and the remaining 27.5% influenced by other factors that are not present in this research. Suggested to the District Education Office Rokan Hulu for more attention to the function of teaching and learning facilities and the performance of teachers in every school, especially in Elementary school because the lack of lighting facilities, students facilities in classroom or field, and the lack of learning with media approach.Keywords: Facilities and Performance